The strategy for management and control of COVID-19 with the cooperation of all sectors, Yala Province - Tokilay, Rusila (Disease Control Journal, 2024)
Since the outbreak of the Coronavirus Disease 2019 (COVID -19) occurred globally, Yala province has proactively implemented comprehensive management strategies and leveraged collaboration across sectors to curb the impact of the Coronavirus outbreak. The initial outbreak in Yala was reported in March 2020, stemming from religious activities, prompted the declaration of a public health emergency by the Ministry of Public Health. Subsequently, on January 23rd, 2020, Yala Province established an emergency response center, chaired by the governor of Yala Province and Yala Provincial Chief Medical Officer served as a secretary. The objective of this study is to analyze the strategies and measures for preventing and controlling COVID-19 in Yala province during the years 2020-2023. The study was conducted by document analysis and content analysis. Results revealed that the successful integration of operational strategies across administrative and public health departments was presented through the incident command center. Yala Province's incident command center led by the Provincial Communicable Disease Committee had executed 6 proactive operational strategies. People cooperate in disease control and prevention. Particularly the strategy to increase the coverage of administering the first dose of the COVID-19 vaccine in Yala province and to reach 66.69%, which was a higher rate than those of Pattani and Narathiwat provinces. Recommendations for further improvement in management strategies are proposed, Emphasis is placed on developing business continuity plan (BCP) in every sector to ensure effective preparedness and communication with people in the community which will lead to resilient and sustainable response to future challenges.